(untitled) (Global Journal of Medical Research, 2020)
The objective of this study was to describe the risk factors and ethiology (pathogen species and their antimicrobial susceptibility, and identifying of multidrug-resistant microorganisms-MDR) for the oropharyngeal colonization in a Brazilian hospital. A total of 39 patients were analysed, and presented media age of the 57,7 years and media of the duration of hospitalization the 9,2 days. Streptococcus sp. (39,1%) and Staphylococcus aureus (18,9%) were the mains pathogens of clinical significance detected. This study showed high rates of isolated MDR bacteria, which included methicillin-resistant Staphylococcus aureus (MRSA) (71,4%). The use of the antibiotics, the advanced age and the previous hospitalization were the significant risk factors for the oropharyngeal colonization with MDR bacteria in the statistical analysis. These results reinforce the need for a revised protocol for regulation of antibiotic dispensing, and attention for this population profile, that can develop healthcare-associated infections (HAI) from oropharyngeal colonization with MDR bacteria.